Dynamics of Baduy culture in facing global developments in Kanekes Village, Leuwidamar District, Lebak Regency, Banten Province - Babul Bahrudin; Achmad Zurohman (Institut Pendidikan Indonesia, 2021)
This research aims to analyze the dynamics of Baduy culture in facing global developments. The location of this research is Kanekes Village, Leuwidamar District, Lebak Regency, Banten Province. This research uses a qualitative approach. Data collection techniques were carried out through in-depth interviews, observation and documentation. Data validity uses source triangulation and theory triangulation techniques. Data analysis techniques use data collection, data reduction, data presentation, and data verification or conclusions. The focus of the study in this research is to analyze the reality of the Baduy tribe facing global developments in terms of 1) knowledge systems, 2) living equipment and technology systems, and 3) livelihood systems. The results of this research indicate that elements of Baduy culture in the midst of global development are starting to change. Many Baduy people have violated the customary laws that previously served as their way of life. The changes that have occurred can be seen from changes in living equipment systems and technology that have begun to modernize, changes in knowledge systems, and livelihoods that have also changed. These changes in cultural elements are due to several factors, including the large number of tourists, government policies for national development, and developments in communication technology that are starting to enter the Baduy tribal area.